Family Comes First: An Investigation on Entrepreneurial Intention among Chinese Indonesian Gen Z - Kunthi Afrilinda Kusumawardani; Richard Richard (International Journal of Family Business Practices, 2020)
Family and education have often been studied by numerous researchers as the factors of entrepreneurs’ creation. The research discusses the influence of background of family and education in entrepreneurship on the entrepreneurial self-efficacy in shaping the entrepreneurial intention among Chinese Indonesian Gen Z. Through the application of the Theory of Planned Behaviour (TPB), this research employed quantitative method design. This current study uses Structural Equation Modelling (SEM) analysis of 202 individuals. The finding indicates that Family Background and Entrepreneurship Education affect Entrepreneurial Self-Efficacy, and Entrepreneurial Self-Efficacy mediates the relationship between Family Background and Entrepreneurship Education in Entrepreneurial Intention. However, Family Background and Entrepreneurship Education do not have direct influences on Entrepreneurial Intention. Based on the finding, it can be determined that Family Background and Entrepreneurship Education will stimulate a high Entrepreneurial Self-Efficacy which leads to Entrepreneurial Intention. Thus, this study suggests the stakeholder in education in Indonesia create an entrepreneurship-based system in the education curriculum to equip students with knowledge of entrepreneurship and develop the skills not only to discover the business opportunity, but also to create a sustainable one, and at the same time encouraging them to have self-confident in their capability in becoming thriving entrepreneurs. While the finding on Family Background signify that entrepreneurs are nurture, not nature since they need to be stimulated along with Entrepreneurship Education and Self-Efficacy. The limitation of this study lies in the size of the sample, thus future research is recommended to take a larger sample to get more representable data to envisage the Entrepreneurial Intention. This study provides an insight into the Entrepreneurial Intention among Chinese Indonesian Gen Z which has never been investigated in the past. Additionally, it contributes the empirical evidence of Entrepreneurial Self-Efficacy role in transforming Family Background and Entrepreneurship Education into Entrepreneurial Intention.